Current evidence for endovascular therapy in stroke and remaining uncertainties. (21st September 2017) - Motyer, R.; Asadi, H.; Thornton, J.; Nicholson, P.; Kok, H. K.
Abstract: Class 1 level A evidence now supports endovascular thrombectomy as best practice in the management of large vessel occlusion acute ischaemic stroke. However, significant questions pertaining to initial imaging, radiological assessment, patient selection and therapeutic limits remain unanswered. A specific cohort of patients who benefit from endovascular thrombectomy has been established, although current uncertainties regarding selection of those not meeting top‐tier evidence criteria may potentially deny certain patients the benefit of intervention. This is of particular relevance in patients presenting in a delayed manner. Whilst superior outcomes are achieved with reduced time to endovascular reperfusion, denying patients intervention based on symptom duration alone may not be appropriate. Advanced understanding of ischaemic stroke pathophysiology supports an individualized approach to patient evaluation, given variance in the rate of ischaemic core progression and the extent of salvageable penumbra. Physiological imaging techniques may therefore be utilized to better inform patient selection for endovascular thrombectomy and evidence suggests that a transition from time‐based to tissue‐based therapeutic thresholds may be of greater value. Multiple ongoing randomized controlled trials aim to further define the benefit of endovascular thrombectomy and it is hoped that these results will advance, and possibly broaden, patient selection criteria to ensure that maximum benefit from the intervention may be achieved.